(untitled) (Research, Society and Development, 2021)
Introduction: Sexually transmitted infections (STI) have consequences that negatively affect the population’s quality of life and health. Young adults are susceptible to low access to preventive measures and a greater behavior risk. The objective was to evaluate and compare STI’ Knowledge in university students from health courses, a public institution, and a private institution of higher education in Brazil. Methods: a cross-sectional study conducted in 2019 in Brazil at the FEMA School of Medicine in Assis-SP and the University of the State of São Paulo (UNESP) in Marília in the courses of Physiotherapy, Speech Therapy, and Occupational Therapy, in undergraduate students, over 18 years of age, through a self-applied questionnaire translated and adapted to the Brazilian Portuguese from the STD-KQ – Transmitted Disease Knowledge Questionnaire.Results: 462/700 students participated (66.66%) 18-46 years of age (mean 21.46 years, +/- 3.61), 99 men and 363 women. In the private institution, 262/340 (77.06%), and in the public institution, 200/360 (55.55%). The mean age was 22.21 (+/- 4.21) years among men and 21.25 (+/- 3.41) years among women. The mean percentage of the 28 test questions’ correct answers was 52.07%. The average number of correct responses per student was 17.49 out of 28 possible, 62% (+/-4.97). The distribution between the groups was normal. In the multiple linear regression model for the percentage of correct answers, adjusted for the confounding variables, the intercept was 55.2. The students of the private institution answered 19,655 questions more than the public one (P<.001), and for each semester of graduation, the students answered 1,628 more questions (P<.001). There were no relevant differences regarding the gender and age of the students. Conclusion: there are gaps in STI knowledge among university students in the health area. The students of the first semesters of the courses, and, in particular, students from a public educational institution, had a significantly lower performance of the right in the questionnaire applied. Thus, actions to promote STI knowledge and preventive attitudes are necessary among university students.